The wood-decaying fungal diversity unveiled by morphology and phylogeny in Ailaoshan Mountain, Yunnan, China - Wang, Lu; Yang, Xin; Zhao, Changlin (Phytotaxa, 2024)
Seven field surveys were carried out in the Ailaoshan area of Yunnan Province, China, from 2016 to 2021, in which 2,814 specimens of wood-decaying fungal species were collected and identified based on morphology and phylogenetic analyses. One hundred and three wood-decaying species were identified, belonging to 64 genera, 29 families, and nine orders. Polyporales is the most abundant order in this area, accounting for 55.34% of all species, while Polyporaceae is the most abundant family, accounting for 18.45% of all species discovered in this area. The wood-decaying fungal checklist is provided according to the latest fungi classification system. Of these species, 11 are edible and therapeutic, four are forest pathogens, eight are threatened, and nine have just been reported from Ailaoshan Mountain. These species comprise 10.68%, 3.88%, 7.77%, and 8.74% of all species, respectively, while 71 species, or 68.93%, have unclear functional relationships. The sequences of the Internal Transcribed Spacer (ITS) gene region of the studied specimens were generated, and the phylogenetic analyses were performed with the maximum likelihood, maximum parsimony, and Bayesian inference methods. This study enriches the diversity of wood-decaying fungi in the Ailaoshan area. Also, it provides a theoretical basis for the future protection and utilization of wood-decaying fungal resources in this area.